The Tourist and Recreational Activity of the Financial Elite in Poland - Alejziak, Wiesław (Turyzm/Tourism, 2001)
Data on the tourist preferences, and the level and structure of the Polish financial elite’s tourist consumption, is not reported in official statistics. Such a situation places many obstacles in the way of the tourist market and makes it difficult to determine the compatibility of the offer with this elite’s structure of consumer needs and motivation. The research presented in this article was conducted to identify the tourist preferences and circumstances, and the level and structure of tourist activities, of the wealthiest Polish business people.